4CPS-225 The role of clinical pharmacists monitoring regarding the effectiveness and tolerance of expensive drugs prescribed off-label. (March 2019) - Guillot, C; Gutermann, L; Djoudi, L; Lopez, I; Batista, R; Conort, O
Abstract : Background: Since 2015 in our French hospital, prescribers must fill out a justifying form (JF) for each off-label initiation of expensive treatments. The medical and financial follow-up is carried out by clinical pharmacists regarding chronic diseases. Furthermore, the patient must be informed about the off-label use of his treatment, and the JF must be included in the patient's file. Purpose: In this context, a retrospective study was performed over 2 years to ensure the justified maintenance of off-label treatments in terms of effectiveness, tolerance and cost. Material and methods: The off-label JF includes references to publications, clinical argument, criteria of effectiveness and tolerance. For each chronic indication, the tracability of the JF, and the evaluation of effectiveness and tolerance were researched in the computerised patient file (Orbis). The 2016 and 2017 dispensing data and treatment costs were extracted from Phedra software. Results: Seventy-seven patients were involved with 63 JF found (82%). Ninety-three per cent of the files were archived at the pharmacy, but none were found in Orbis. Only 17.5% of the JF were fully completed. The most filled item was the clinical argument (86%) and the least filled item was the date of the multidisciplinary consultation meeting (43%). Sixty-three patients had a chronic condition. The most prescribed treatments were Tocilizumab, Adalimumab, Infliximab and intravenous immunoglobulin, mostly in the internal medicine and rheumatology departments. Horton and Behçet diseases, hypogammaglobulinaemia, sarcoidosis and undifferenciated inflammatory arthritis were the most common indications. Effectiveness data were evaluated for 52 patients: 77% of effectiveness (including four healings), 19% of interruptions for ineffectiveness and 4% for adverse effects. A subcutaneous relay was observed in seven cases. The hospital cost was estimated at €7 35 000 (including Canakinumab €191, 000). Conclusion: Off-label initiations are mostly justified. The reformulation of some items of the JF and its computerisation in Orbis are necessary in improving traceability. Clinical effectiveness is found in more than two-thirds of chronic off-label prescriptions. Horton and Behçet's diseases have recently obtained their label, strengthening the validity of these prescriptions. The clinical pharmacist monitoring of treatment effectiveness and safety permits a quick discontinuation in expensive and inefficient treatment. References and/or acknowledgements: No conflict of interest.